Antioxidant and metabolite identification of different varieties of dates (Phoenix dactylifera L.) - Kadum, Hana; Abdul Hamid, Azizah; Abas, Faridah; Mohammed, Abdulkarim Sabo; Ramli, Nurul Shazini (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Date fruits are important for both nutritional and therapeutic properties. They are rich sources of sugars, vitamins, minerals, fibres and various phytochemicals. The aim of this study is to determine the antioxidant activity and metabolite profiling of 5 different dates (Phoenix dactylifera L.) varieties including Ajwa, Mariami, Piyarom, Tunisia, and Anbar. The antioxidant activity of the dates was measured using DPPH, FRAP assay systems. Proton nuclear magnetic resonance (1H NMR) was used for metabolite profiling. Results of the study revealed that Mariami extract consisted of the highest total phenolic content (355 mg GAE/g DW), while the most potent DPPH scavenging activity (IC50 of 16.2 μg/mL) and FRAP (18.38 Mm Fe (II)/g) was demonstrated by Piyarom variety. A discriminatory study on metabolites responsible for the variation between the samples was successfully performed using 1H-NMR-based metabolomics. The principal component analysis plots exhibited clear and distinct separations between the dates studied. The metabolites identified that may attribute to the separation were sucrose, succinic acid, leucine, glutamine and lysine. The results suggest that all the studied dates serve as a good source of vital nutrients and can be considered as a premium quality having significantly higher antioxidant activity.